Activity and income diversification: trends, determinants and Effects on Poverty Reduction:The Case of the Mekong River Delta = Disversificateie van activiteniten en inkomen : trends, determinaten en efecten op armoebestijding de situatie in de Mekong rivirdelta - Le Tan Nghiem (Shaker Publishing B.V., 2010)
The book on diversification of activities and income: with issues such as trends, determinants and implications for business poverty alleviation in the Mekong Delta